Challenges of eHealth and Current Developments in eHealth Applications: An Overview - V., Saikumari; A., Arunraj (EAI Endorsed Transactions on Smart Cities, 2022)
Healthcare sector is moving towards digitalization in every aspect including e-consultations, surveillance of health,and all other services in healthcare industry. eHealth ends in the remodel of conventional methods of imparting specialist healthcare offerings digitally through the use of technology aimed toward both fee-effectiveness and patient satisfaction who are the customers of health offerings. Electronic health records has been maintained by developed countries which makes evaluating patient outcome easier. which makes evaluation of patient outcomes much easier. In the health sector, a variety of new ICTs are implemented to improve the efficiency of all levels of healthcare. eHealth—or digital health—is the use of ICT to improve the ability to treat patients, facilitate behaviour change, and improve health. Advances in information and communication technology (ICT) and the dissemination of network data processing created a new environment of universal access to information and globalization of communications, businesses, and services eHealth applications were analysed to determine the brand new developments in E-health programs. In this paper, the stakeholders are identified who’re accountable for contributing to a selected eHealth challenge. By analysing the current scenario of E-health, we identified the challenges faced by eHealth technologies. The factors influencing the challenges were identified and classified. The emerging trends in the field of e-Health was studied and the applications and its benefits towards the patients was also analysed. The paper also elaborates on the role of mHealth in eHealth.